A study on adulteration in cereals and bakery products from Poland including a review of definitions. (October 2018) - Kowalska, Aleksandra; Soon, Jan Mei; Manning, Louise
Abstract: The aim of the study was to critique the food adulteration trends associated with cereals and bakery products from Poland. The methodological approach was to firstly review existing literature to define and outline the challenge of food adulteration and the degree of harmonisation, or not, of definitions, and then to analyse local and European data on the prevalence of food adulteration and mislabelling in the cereals and bakery sector more generally, and specifically in Poland. Analysis of general RASFF notifications of cereal and bakery products linked to Poland (n = 177) revealed that most non-compliances were due to mycotoxins, undeclared allergens and undeclared genetically modified materials. Key notable trends included an increase in incorrect allergen labelling with only two incidents directly associated with adulteration firstly with melamine and also suspicion of deliberate contamination of milk powder with rodenticide. Data from IJHARS share similar trends where most reported irregularities associated with cereal and bakery products were related to mislabelling. The definition of adulterated foodstuffs in Poland concentrates on mislabelling particularly regarding product composition rather than being differentiated by the motivation of the perpetrator. This is not in step with other definitions where intent is seen an inherent aspect of a determination of an instance of food fraud or adulteration. This work demonstrates that even in harmonized regulatory areas such as the EU there are local definitions of adulteration that due to the lack of consistency could influence collective approaches to determining the extent of or addressing the problem of mislabelling, misrepresentation and misbranding as a form of adulteration. Highlights: Most commonly reported adulterated cereal and bakery products in Poland were bread and pasta. Most cases of food adulteration were related to mislabelling. More research needed to contextualise drivers for mislabelled and misrepresented products.